Nucleophilic functionalization of thianthrenium salts under basic conditions - Fan, Xinting; Zhang, Duo; Xiu, Xiangchuan; Xu, Bin; Yuan, Yu; Chen, Feng; Gao, Pan (Beilstein Journal of Organic Chemistry, 2024)
In recent years, S-(alkyl)thianthrenium salts have become an important means of functionalizing alcohol compounds. However, additional transition metal catalysts and/or visible light are required. Herein, a direct thioetherification/amination reaction of thianthrenium salts is realized under metal-free conditions. This strategy exhibits good functional-group tolerance, operational simplicity, and an extensive range of compatible substrates.
Keywords: amination; functionalization of alcohol; metal-free; S-(alkyl)thianthrenium salts; thioetherification